TOWARDS SUSTAINABLE HEALTHCARE IN MALAYSIA: UNVEILING ESSENTIAL DETERMINANTS - Wan Zulia Zafini Wan Zulkifli; Norshahrizan Nordin; Ehab Aktham Kassab (Journal of Human Development and Communication (JoHDeC), 2025)
The need for a sustainable healthcare system in Malaysia has become more pressing due to the growing demand for healthcare services and changing societal requirements. This urgency is driven by the goals set under Sustainable Development Goal 3 (SDG3), to be achieved by 2030. Malaysia faces significant challenges in its healthcare sector, closely linked to this global issue. The sustainability of healthcare services is intricately tied to the relationship of social support, cultural factors, and economic changes. Therefore, constructing resilient healthcare systems capable of withstanding unforeseen challenges, such as pandemics, necessitates a comprehensive approach that takes into account these multifaceted factors. This paper aims to introduce a conceptual framework centered around social support, cultural factors, and economic changes in the context of healthcare sustainability in Malaysia. This framework emphasizes the importance of robust social support systems, cultural competence, and economic adaptability in ensuring healthcare service sustainability. This study sheds light on the pivotal determinants of healthcare service sustainability, aligning with the objectives of SDG3. It highlights the urgent need for policy reforms, cross-sector collaboration, and economic alignment to effectively address these multifaceted challenges and ensure the achievement of healthy lives and well-being for all.